Mucuna pruriens Linn. seed extract pretreatment protects against cardiorespiratory and neuromuscular depressant effects of Naja sputatrix (Javan spitting cobra) venom in rats - Fung, S.Y.; Tan, N.H.; Sim, S.M.; Marinello, E.; Guerranti, R. (2011)
Mucuna pruriens has been used by native Nigerians as a prophylactic for snakebite. The protective effects of M. pruriens seed extract (MPE) were investigated against the pharmacological actions of N. sputatrix (Javan spitting cobra) venom in rats. The results showed that MPE-pretreatment protected against cardiorespiratory and, to a lesser extent, neuromuscular depressant effects of N. sputatrix venom. These may be explained at least in part by the neutralisation of the cobra venom toxins by anti-MPE antibodies elicited by the MPE pretreatment.